How to manage osteoporosis before the age of 50. (August 2020) - Rozenberg, S.; Bruyère, O.; Bergmann, P.; Cavalier, E.; Gielen, E.; Goemaere, S.; Kaufman, J.M.; Lapauw, B.; Laurent, M.R.; De Schepper, J.; Body, J.J.
Highlights: The puberty constitutes a vulnerable period during which Peak Bone Mass can be affected. Diagnosis and management of osteoporosis in the young can be challenging. Secondary causes of excessive bone loss need to be excluded. Young adults with low bone mineral density do not necessarily need to be treated. Abstract: This narrative review discusses several aspects of the management of osteoporosis in patients under 50 years of age. Peak bone mass is genetically determined but can also be affected by lifestyle factors. Puberty constitutes a vulnerable period. Idiopathic osteoporosis is a rare, heterogeneous condition in young adults due in part to decreased osteoblast function and deficient bone acquisition. There are no evidence-based treatment recommendations. Drugs use can be proposed to elderly patients at very high risk. Diagnosis and management of osteoporosis in the young can be challenging, in particular in the absence of a manifest secondary cause. Young adults with low bone mineral density (BMD) do not necessarily have osteoporosis and it is important to avoid unnecessary treatment. A determination of BMD is recommended for premenopausal women who have had a fragility fracture or who have secondary causes of osteoporosis: secondary causes of excessive bone loss need to be excluded and treatment should be targeted. Adequate calcium, vitamin D, and a healthy lifestyle should be recommended. In the absence of fractures, conservative management is generally sufficient, but in rare cases, such as chemotherapy-induced osteoporosis, antiresorptive medication can be used. Osteoporosis in young men is most often of secondary origin and hypogonadism is a major cause; testosterone replacement therapy will improve BMD in these patients. Diabetes is characterized by major alterations in bone quality, implying that medical therapy should be started sooner than for other causes of osteoporosis. Primary hyperparathyroidism, hyperthyroidism, Cushing's syndrome and growth hormone deficiency or excess affect cortical bone more often than trabecular bone.